To Compare the Kidney Dimensions in Healthy Individuals with Acute and Chronic Pyelonephritis Patients Using CT Scan as an Imaging Modality - Siddiqui, Hania; Shaukat, Shaista; Raza, Iffar; Faiz, Samira; Siddiqui, M Nadeem; Mehmood, Tariq (Biological and Clinical Sciences Research Journal, 2025)
Acute or chronic pyelonephritis is a common renal pathology that can lead to significant kidney morphological changes. Accurate assessment of renal dimensions using imaging modalities such as computed tomography (CT) is essential for diagnosis and management. However, limited data on normal kidney dimensions and their variation in pyelonephritis in the adult Pakistani population are available. Objective: To compare normal kidney dimensions in healthy individuals with those in patients diagnosed with acute and chronic pyelonephritis on CT scan in the adult Pakistani population, and to correlate kidney size with age and gender. Methods: This case-control study was conducted at the Radiology Department of Jinnah Postgraduate Medical Centre, Karachi, over six months from September 2023 to February 2024. A total of 126 adults were included using a consecutive non-probability sampling technique: 77 healthy individuals (controls) and 49 patients diagnosed with acute or chronic pyelonephritis based on CT findings. Renal dimensions were measured using axial, coronal, and sagittal slices from multislice CT scans. Kidney lengths and transverse diameters were recorded. Statistical analysis was performed using the independent t-test to compare kidney dimensions between cases and controls and acute and chronic pyelonephritis groups. A p-value < 0.05 was considered statistically significant. Results: The mean age of patients with pyelonephritis was 45.8 ± 12.0 years. The mean transverse diameter of the right kidney in pyelonephritis cases was significantly larger (5.05 ± 0.18 cm) compared to controls (4.34 ± 0.06 cm) (p = 0.001). Among the pyelonephritis group, the mean transverse dimension of the left kidney in acute cases was 5.52 ± 1.00 cm, significantly larger than in chronic cases (4.44 ± 1.05 cm) (p = 0.001). Similarly, the right kidney in acute pyelonephritis had a mean transverse diameter of 5.52 ± 1.20 cm compared to 4.48 ± 0.65 cm in chronic pyelonephritis (p = 0.001). Conclusion: The study demonstrated that kidneys in patients with acute pyelonephritis are significantly swollen, whereas chronic infections are associated with renal atrophy. Additionally, the parenchymal thickness in pyelonephritis patients was significantly greater than in healthy controls. CT imaging is reliable for distinguishing between acute and chronic renal changes in pyelonephritis based on kidney dimensions.